Wakaf Muhammadiyah dalam Membangun Pendidikan Berkemajuan di SMP Muhammadiyah Ahmad Dahlan Kota Metro - Nurul Mahmudah; Dea Tara Ningtyas; Supiah Supiah; Julduz R Paus (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2020)
The writing of this research aims to explain the management and impact of waqf for education in SMP Muhammadiyah Ahmad Dahlan Metro City. As for the background in this writing is the demands and expectations of the community for the greater quality of education but the capacity of the government is not yet worth the demand of the community. So the waqf movement became one of the alternatives offered to answer the challenge. Waqf movement, especially in SMP Muhammadiyah Ahmad Dahlan aims to improve the quality of education in accordance with Muhammadiyah jargon namely